2003
DOI: 10.1103/physrevb.67.184402
|View full text |Cite
|
Sign up to set email alerts
|

Growth morphology, structure, and magnetism of ultrathin Co films on W(111)

Abstract: The growth morphology, structure, and magnetism of ultrathin Co films on the W͑111͒ surface are studied with conventional and spin polarized low energy electron microscopy and diffraction and first principles total energy calculations. Pseudo-layer-by-layer growth of thick pseudomorphic ͑ps͒ Co films is observed at 380 K, while Stranski-Krastanov growth and transformation to a ͑6ϫ6͒ closed-packed structure are observed at higher temperatures. On the basis of the calculations, only one ps Co monolayer is expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Besides, tungsten-based devices have been extensively studied and applied in spin detector and single atom tip, due to the high thermal stability of tungsten. 9 [13][14][15] However the preparation of a magnetic nano-pyramid on the tip point is still challenging, and the study of the related magnetic properties is lacking. This leads us to the investigation of magnetic coverage on the Pd/W{112} faceting surface.…”
mentioning
confidence: 99%
“…Besides, tungsten-based devices have been extensively studied and applied in spin detector and single atom tip, due to the high thermal stability of tungsten. 9 [13][14][15] However the preparation of a magnetic nano-pyramid on the tip point is still challenging, and the study of the related magnetic properties is lacking. This leads us to the investigation of magnetic coverage on the Pd/W{112} faceting surface.…”
mentioning
confidence: 99%
“…75,76 Spin polarized LEEM can probe both in and out of plane magnetization by means of the spin dependent exchange scattering. 77 A final direction of research which will benefit from PEEM and LEEM techniques is the behavior and the characterization of structures on device scales. Using suitable, customized sample holders, it is possible to wire up for example a single microscopic capacitor and, using the high spatial resolution study its response to current or voltage.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Man et al reported the growth morphology, structure, and magnetism of Co films on clean W(111) surface by spinpolarized low energy electron microscope (SP-LEEM) and LEED. 19 Pseudo-layer-by-layer growth of Co films was observed at 380 K, while Stranski-Krastanov growth was observed at higher temperature. However, based on their calculation but contradicting the conclusion of Guan et al, only one pseudomorphic layer (¼1/3 PML) was predicted to be thermodynamically stable against 3D island formation.…”
Section: Introductionmentioning
confidence: 91%
“…17,18 Despite the above promising applications, there are only a few studies reporting magnetic transition metals on the W(111) surface. 10,[19][20][21] In 1996, the structure and morphology of Co films on a clean W(111) surface were reported by Guan et al using low energy electron spectroscopy (LEED) and Auger electron spectroscopy (AES). Pseudomorphic Co films were grown at room temperature (RT) with thickness up to 4 PML.…”
Section: Introductionmentioning
confidence: 97%